The hematopoietic stem cell marker VNN2 is associated with chemoresistance in pediatric B-cell precursor ALL - Bornhauser, Beat; Cario, Gunnar; Rinaldi, Anna; Risch, Thomas; Rodriguez Martinez, Virginia; Schütte, Moritz; Warnatz, Hans-Jörg; Scheidegger, Nastassja; Mirkowska, Paulina; Temperli, Martina; Möller, Claudia; Schumich, Angela; et al. (Blood advances, 2020)
Most relapses of acute lymphoblastic leukemia (ALL) occur in patients with a medium risk (MR) for relapse on the Associazione Italiana di Ematologia e Oncologia Pediatrica and Berlin-Frankfurt-Münster (AIEOP-BFM) ALL protocol, based on persistence of minimal residual disease (MRD). New insights into biological features that are associated with MRD are needed. Here, we identify the glycosylphosphatidylinositol-anchored cell surface protein vanin-2 (VNN2; GPI-80) by charting the cell surface proteome of MRD very high-risk (HR) B-cell precursor (BCP) ALL using a chemoproteomics strategy. The correlation between VNN2 transcript and surface protein expression enabled a retrospective analysis (ALL-BFM 2000; N = 770 cases) using quantitative polymerase chain reaction to confirm the association of VNN2 with MRD and independent prediction of worse outcome. Using flow cytometry, we detected VNN2 expression in 2 waves, in human adult bone marrow stem and progenitor cells and in the mature myeloid compartment, in line with proposed roles for fetal hematopoietic stem cells and inflammation. Prospective validation by flow cytometry in the ongoing clinical trial (AIEOP-BFM 2009) identified 10% (103/1069) of VNN2+ BCP ALL patients at first diagnosis, primarily in the MRD MR (48/103, 47%) and HR (37/103, 36%) groups, across various cytogenetic subtypes. We also detected frequent mutations in epigenetic regulators in VNN2+ ALLs, including histone H3 methyltransferases MLL2, SETD2, and EZH2 and demethylase KDM6A. Inactivation of the VNN2 gene did not impair leukemia repopulation capacity in xenografts. Taken together, VNN2 marks a cellular state of increased resistance to chemotherapy that warrants further investigations. Therefore, this marker should be included in diagnostic flow cytometry panels.
Keywords: Drug Resistance, Neoplasm; akutní lymfatická leukemie; dítě; molekuly buněčné adheze; Hematopoietic Stem Cells; GPI-vázané proteiny; lidé; chemorezistence; Antineoplastic Combined Chemotherapy Protocols; protokoly protinádorové kombinované chemoterapie; retrospektivní studie; Amidohydrolases; prospektivní studie; Prospective Studies; GPI-Linked Proteins; Cell Adhesion Molecules; hematopoetické kmenové buňky; B-Lymphocytes; B-lymfocyty; Precursor Cell Lymphoblastic Leukemia-Lymphoma; Child; Retrospective Studies; amidohydrolasy; Humans